In vitro evaluation of drying supports and adhesive polymers as adjuvants for biocontrol of Diplodia seriata by Trichoderma harzianum and Clonostachys rosea - AGUIRRE, Katherina; PEREZ, Luz M.; MONTEALEGRE, Jaime R. (Phytopathologia Mediterranea, 2023)
Grapevine trunk diseases (GTDs) can cause large losses in vineyards. Diplodia seriata is an important GTD pathogen in Chile. Development and use of bioprotectors is a complementary alternative to the use of agrochemicals for disease management. To produce bioformulations for management of D. seriata, additives could be used to maintain viability and survival of biocontrol agents, such as Trichoderma harzianum and Clonostachys rosea. Effects of drying supports (inulin, maltodextrin, lactose, or talc) and adhesive polymers (carboxymethylcellulose, Aloe vera gel, or chitosan) were assessed on D. seriata conidium viability and mycelium development of T. harzianum and C. rosea, and for their biocontrol capacity against D. seriata. T. harzianum and C. rosea cultured in Potato Dextrose Agar containing inulin (at 10% w/v) maltodextrin (10% w/v), lactose (6% w/v), or talc (4% w/v), or the adhesive polymers carboxymethylcellulose (0.5% w/v), Aloe vera gel (0.5% w/v), or chitosan (1.5% w/v), maintained their biocontrol activity against D. seriata. These additives did not enhance D. seriata development. Therefore, these preparations, at the respective indicated concentrations, can be included in bioformulations for management of disease caused by this pathogen.